Manajemen Supervisi Akademik Kepala Madrasah Di Mts Mazro'atul Ulum Citiis - Ahmad Ghozali Panjaitan; Asy’ari Asy’ari; Afifah Barkatul Atqiya; Muhammad Amar Khana (Peneliti.net, 2023)
This study aims to determine the management of headmaster academic supervision, headmaster academic supervision planning, the implementation of academic supervision of the principal, and the evaluation and follow-up of the academic supervision of the principal. This study uses a qualitative approach. Data collection techniques through observation, interviews, documentation. The research subjects were the head of the madrasa and the teacher. The results of the study showed: profile of education in Bandung Barat 2 Islamic Elementary School preparation of academic supervision programs arranged at the beginning of the school year by including teachers. Academic supervision program is arranged based on the problems faced by the teacher about learning and adjusting to the needs of the teacher; implementation of academic supervision in accordance with programs that have been prepared using several supervision techniques including individual techniques and group techniques; evaluation is carried out by looking at the results of the planning and implementation of academic supervision programs implemented and follow-up conducted by the headmaster by providing guidance to teachers who have not met standards and awards to teachers who meet the standards; and factors supporting and inhibiting the academic supervision of the headmaster. Based on the results of these studies, the implementation of the headmaster's academic supervision in improving teacher performance in Bandung Barat 2 Islamic Elementary School has not been well implemented in improving teacher performance. Keywords : Management, Academic Supervision, Head Master.